A multi-center, randomized, clinical trial comparing adhesive polyurethane foam dressing and adhesive hydrocolloid dressing in patients with grade II pressure ulcers in primary care and nursing homes - Guillén-Solà, Mireia (BioMed Central, 2013)
BACKGROUND: Pressure ulcers (PrUs) are ischemic wounds in the skin and underlying tissues caused by long-standing pressure force over an external bone or cartilaginous surface. PrUs are an important challenge for the overall health system because can prolong patient hospitalization and reduce quality of life. Moreover, 95% of PrUs are avoidable, suggesting they are caused by poor quality care assistance. PrUs are also costly, increasing national costs. For example, they represent about 5% of overall annual health expenses in Spain. Stages I and II PrUs have a combined prevalence of 65%. According main clinical guidelines, stage II PrUs (PrU-IIs) are usually treated by applying special dressings (polyurethane or hydrocolloid). However, little scientific evidence regarding their efficacy has been identified in scientific literature. Our aim is to assess the comparative efficacy of adhesive polyurethane foam and hydrocolloid dressings in the treatment of PrU-IIs in terms of healed ulcer after 8 weeks of follow-up. METHODS/DESIGN: This paper describes the development and evaluation protocol of a randomized clinical trial of two parallel treatment arms. A total of 820 patients with at least 1 PrU-II will be recruited from primary health care and home care centers. All patients will receive standardized healing procedures and preventive measures (e.g. positional changes and pressure-relieving support surfaces), following standardized procedures. The main outcome will be the percentage of wounds healed after 8 weeks. Secondary outcomes will include cost-effectiveness, as evaluated by cost per healed ulcer and cost per treated patient and safety evaluated by adverse events. DISCUSSION: This trial will address the hypothesis that hydrocolloid dressings will heal at least 10% more stage II PrUs and be more cost-effective than polyurethane foam dressings after 8 weeks. TRIAL REGISTRATION: This trial has been registered with controlled-trials number ISCRCTN57842461 and EudraCT 2012-003945-14.